Predictors of Progression in Barrett’s Esophagus II: Baseline 17p (p53) Loss of Heterozygosity Identifies a Patient Subset at Increased Risk for Neoplastic Progression - Reid, Brian J. (2001)
OBJECTIVES: Most patients with Barrett’s esophagus do not progress to cancer, but those who do seem to have markedly increased survival when cancers are detected at an early stage. Most surveillance programs are based on histological assessment of dysplasia, but dysplasia is subject to observer variation and transient diagnoses of dysplasia increase the cost of medical care. We have previously validated flow cytometric increased 4N fractions and aneuploidy as predictors of progression to cancer in Barrett’s esophagus. However, multiple somatic genetic lesions develop during neoplastic progression in Barrett’s esophagus, and it is likely that a panel of objective biomarkers will be required to manage the cancer risk optimally. METHODS: We prospectively evaluated endoscopic biopsies from 325 patients with Barrett’s esophagus, 269 of whom had one or more follow-up endoscopies, by a robust platform for loss of heterozygosity (LOH) analysis, using baseline 17p (p53) LOH as a predictor and increased 4N, aneuploidy, high-grade dysplasia, and esophageal adenocarcinoma as outcomes. RESULTS: The prevalence of 17p (p53) LOH at baseline increased from 6% in negative for dysplasia to 57% in high-grade dysplasia (p < 0.001). Patients with 17p (p53) LOH had increased rates of progression to cancer (relative risk [RR] = 16, p < 0.001), high-grade dysplasia (RR = 3.6, p = 0.02), increased 4N (RR = 6.1, p < 0.001), and aneuploidy (RR = 7.5, p < 0.001). CONCLUSIONS: Patients with 17p (p53) LOH are at increased risk for progression to esophageal adenocarcinoma as well as high-grade dysplasia, increased 4N, and aneuploidy. 17p (p53) LOH is a predictor of progression in Barrett’s esophagus that can be combined with a panel of other validated biomarkers for risk assessment as well as intermediate endpoints in prevention trials.